Supplier Risk Management in Supply Chain Relationships with Preferred Customer Status at Pt Japfa Comfeed Indonesia - Nugroho, Mochammad Arie; Indrawati, Nur Khusniyah; Sudjatno (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research provides a comprehensive risk management framework for supply chain relationships where suppliers have customers who have preferred customer status. This research is a case study research using a qualitative approach on the largest and leading agri-food companies in Indonesia, with several real-life perspectives on key risks, risk impacts, and mitigation strategies for implementing a risk management framework. The research results show that several risks can affect supply chain relationships between customers and suppliers: not only operational risks but also risks associated with specific relationships, as well as risks specific to supply chain relationships with preferred customer status. Creating correct and clear contracts was found to be a core strategy to mitigate risks built to protect supply chain relationships.